Peran Gaya Kepemimpinan Transaksional dan Budaya Organisasi dalam Meningkatkan Kinerja Pegawai di Kantor Pengadilan Agama Kota Gunungsitoli - Nur Aisyah Zebua; Eliagus Telaumbanua; Palindungan Lahagu; Fatolosa Hulu (Lembaga Pengembangan Kinerja Dosen, 2025)
In the era of globalization and increasingly dynamic work competition, organizations are required to have an effective leadership system and work culture to improve employee performance. This research aims to analyze the role of transactional leadership style and organizational culture in improving employee performance at the Gunungsitoli City Religious Court Office. The transactional leadership style is seen as an approach that emphasizes exchanges between leaders and subordinates through providing rewards or sanctions based on performance achievements, while organizational culture reflects the values, norms and habits that shape employee work behavior. Based on the pre-observation results, a number of problems were found, such as the ineffectiveness of the reward system, a mismatch between formal values ​​and real culture, less than optimal communication flow, and a decrease in employee motivation and productivity. This research uses a descriptive qualitative approach to reveal in depth the internal dynamics of the organization, using data collection techniques through observation, in-depth interviews and documentation. The expected result of this research is the preparation of strategic recommendations to increase leadership effectiveness and build a healthy and conducive organizational culture, so as to encourage continuous improvement in employee performance. It is hoped that this research can contribute to the development of human resource management theory and governance practices in public sector organizations, especially in religious justice institutions.